Mario Bellini e il progetto di allestimento della mostra ’Il Tesoro di San Marco’ presentato dalla Olivetti (1984-1987) - Acocella, Alessandra (Opus Incertum, 2024)
The 1980s marked a period of intense collaboration between Mario Bellini and the Olivetti company, encompassing the creation of both design objects and display solutions. Among these was the design for the Treasure of St. Mark exhibition, inaugurated in Paris in March 1984 and subsequently toured in Cologne, London, New York, Los Angeles, Dallas, Chicago, Rome, Milan, and Venice. The event was part of Olivetti’s broader initiative aimed to the preservation and enhancement of the Italian cultural heritage, showcasing a selection of some of the most valuable artifacts from Venice’s collection of Eastern Byzantine and Islamic art, and of Western medieval art. Bellini’s exhibition design emphasized the rarity and uniqueness of the artefacts through innovative display solutions. Central to this approach was the use of pyramid-shaped cases illuminated from above, designed to be mobile and adaptable to different museum contexts, while enveloping the surrounding space in semi-darkness to heighten the visual impact of the exhibits. By analyzing textual and visual sources preserved in the Olivetti Historical Archive Association and the Mario Bellini Architects studio, the article aims to reconstruct and critically examine this exhibition, while investigating the role played by the Olivetti company and the groundbreaking design solutions proposed by the Milanese architect and designer for this occasion.